Early sedentary behavior symptoms investigation on nutrition, physical fitness, and behavioral setting for novice sports science students. - Nugroho, Sigit; Prasetyo, Yudik; Sulistiyono; Mulyawan, Rizki; Nourzad, Fatemeh (Polish Journal of Physiotherapy / Fizjoterapia Polska, 2024)
This study investigates the condition of (1) nutritional status, (2) physical fitness, (3) physical activity patterns of sports science study program students after the pandemic. The research method uses quantitative methods with analytical observational design. The research subjects were sports students from the Sports Science study program, FIKK UNY. The subjects were active students totaling around 50 participants determined using purposive sampling techniques. Physical fitness data collection techniques use the BMI formula, bleep test and GPAQ questionnaire. Techniques for analyzing data with homogeneity and normality. The results obtained from nutritional status and cardiovascular fitness can be said to be still unsatisfactory, nutritional status is in the normal or ideal category, but the range of cardiovascular abilities is still in the adequate category for men and inadequate for women. Meanwhile, the measurement results from filling out the GPAQ questionnaire show that there is still a need to increase awareness of the importance of physical activity, indicated by transportation and recreational activities of moderate intensity which are still in the category of not meeting the recommendations, even though heavy, moderate physical activity and vigorous recreational activities meet the recommendations. Nutritional status is still in the normal category, but the range of cardiovascular abilities is still in the adequate category for men and inadequate for women. This is positively correlated with moderate intensity physical activity patterns, transportation and recreation, which are still in the category of not meeting recommendations. The sedentary habits usually carried out by sports students must be able to be transferred as soon as possible to more useful and productive movement activities. Amount of leisure time for physical activity is still relatively low, whereas other moderate to vigorous physical activity habits are beginning to resurface. There must be an intentional strategy to provide suggestions on how to spend free time performing activities outdoors or indoors.